Kepribadian dan Aktualisasi Diri Tokoh Utama Dalam Novel The Midnight Library Karya Matt Haig: Teori Psikologi Humanistik Abraham Maslow - Wardani, Fitrah Zhoraya Febrianty; Murniviyanti, Liza; Armariena, Dian Nuzulia (ANTHOR: Education and Learning Journal, 2022)
Humanistic Psychology is a theory in psychology that focuses on the problem of human behavior patterns in meeting needs. This study aims to describe the personality and selfactualization of the main character in the novel The Midnight Library by Matt Haig based on Abraham Maslow's theory of Humanistic Psychology. The data source of this research is the novel The Midnight Library by Matt Haig, theoretical books, articles, journals, and literatures relevant to the research. Data collection was carried out using literature study techniques, while data analysis was carried out using qualitative descriptive techniques. The results of the study show the following results. First, the dominant personality in the main character named Nora Seeds in the novel The Midnight Library by Matt Haig includes sensitive, compassionate, and strong or tough personality. Second, self-actualization in the main character Nora Seeds in Matt Haig's novel The Midnight Library which consists of four goals, namely the desire to accept oneself, the desire to accept other people and circumstances, the desire to develop potential, the desire to stay alive.